2004
DOI: 10.1159/000076487
|View full text |Cite
|
Sign up to set email alerts
|

Topical Effectiveness of Molgramostim (GM-CSF) in Sickle Cell Leg Ulcers

Abstract: Background: Leg ulcers are a frequently neglected, severe complication of sickle cell disease (SCD), responsible for significant altering quality of life. The management of leg ulcers remains disappointing. Local application of recombinant human granulocyte-macrophage colony-stimulating factor has been shown to be effective in several types of chronic wound healing. Methods: We report 5 homozygous sickle cell patients with 14 leg ulcers lasting from 1 month to 6 years, treated with topical dripping of molgramo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 3 publications
1
20
0
1
Order By: Relevance
“…Our results support the previous finding that G-CSF is another important factor during ulcer healing period. 33,52) In the study with immunohistochemical stain results of MMPs and TIMP-1, we found the group combined using with ZnSO 4 had lower MMPs and higher TIMP-1 expression. Zn links with Znbinding protein metallothionein as described in previous study.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…Our results support the previous finding that G-CSF is another important factor during ulcer healing period. 33,52) In the study with immunohistochemical stain results of MMPs and TIMP-1, we found the group combined using with ZnSO 4 had lower MMPs and higher TIMP-1 expression. Zn links with Znbinding protein metallothionein as described in previous study.…”
Section: Discussionmentioning
confidence: 84%
“…We did not include non-diabetic group in this study since each of the approach used in the combination has been used extensively to non-diabetic animals. 19,33,[39][40][41] In these previous studies, application of the exogenous growth factors or Zn did not always stimulate the wound healing process, for which one of the reasons is because normal tissue is not defect for these growth factors or nutrients such as Zn. 42) Diabetic induction by STZ and the full-thickness skin wound for the diabetic rats was made as described in the pilot study.…”
Section: Methodsmentioning
confidence: 93%
See 2 more Smart Citations
“…In an attempt to improve wound healing, various agents, including granulocyte macrophage colony-stimulating factor (GM-CSF), basic fibroblast growth factor, and GM-CSF hydrogel, have been used. Although GM-CSF has been applied successfully in treatment of various clinical problems, its application in burn treatment has not been well reported (DorsettMartin 2004;Méry et al 2004;Cianfaran et al 2006).…”
Section: Introductionmentioning
confidence: 99%